Exploring the drivers of green purchase behaviour: the moderating roles of perceived expensiveness and green scepticism - Aydin, Kenan; Altan, Meral Uzunoz; Kose, Sirin Gizem; Cizer, Ece Ozer (INDERSCIENCE ENTERPRISES LTD, 2024)
This research aims to investigate factors affecting green consumption behaviour by utilising theory of planned behaviour and extends the theory by integrating environmental attitude, perceived expensiveness, and green scepticism variables. The results show that environmental attitude, attitude towards purchasing green products, subjective norms, and perceived behaviour control variables determine green product consumption. The study also presents the partial mediator role of attitude towards buying green products in the relationship between environmental attitude and green product purchase behaviour. Furthermore, perceived expensiveness and green scepticism have negative moderating roles in the relationship between attitudes toward purchasing green products and green purchase behaviour.
Keywords: green product; theory of planned behaviour; environmental attitude; green marketing; green consumption; PRODUCTS; EXTENSION; CONSUMERS; ATTITUDE; Environmental Sciences & Ecology